2010
DOI: 10.1038/ejhg.2010.213
|View full text |Cite
|
Sign up to set email alerts
|

A large homozygous deletion in the SAMHD1 gene causes atypical Aicardi–Goutiéres syndrome associated with mtDNA deletions

Abstract: Aicardi-Goutié res syndrome (AGS) is a genetic neurodegenerative disorder with clinical symptoms mimicking a congenital viral infection. Five causative genes have been described: three prime repair exonuclease1 (TREX1), ribonucleases H2A, B and C, and most recently SAM domain and HD domain 1 (SAMHD1). We performed a detailed clinical and molecular characterization of a family with autosomal recessive neurodegenerative disorder showing white matter destruction and calcifications, presenting in utero and associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…The role of Vpx in counteracting APOBEC3A is unclear, but it is possible that under conditions of low dNTP caused by SAMHD1, in which reverse transcription is slowed, APOBEC3A more effectively deaminates nascent reverse transcripts. It is noteworthy that a large homozygous deletion in the SAMHD1 gene has been associated with mitochondrial DNA deletions, as mitochondrial diseases are often the result of mutations in the genes encoding enzymes that are involved in dNTP metabolism 30-32 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of Vpx in counteracting APOBEC3A is unclear, but it is possible that under conditions of low dNTP caused by SAMHD1, in which reverse transcription is slowed, APOBEC3A more effectively deaminates nascent reverse transcripts. It is noteworthy that a large homozygous deletion in the SAMHD1 gene has been associated with mitochondrial DNA deletions, as mitochondrial diseases are often the result of mutations in the genes encoding enzymes that are involved in dNTP metabolism 30-32 .…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these findings support that the extremely low cellular dNTP pool serves as a myeloid cell specific biochemical anti-lentiviral restriction factor, which is maintained by SAMHD1 dNTP triphosphohydrolase activity. Interestingly, genetic alterations in SAMDH1 result in a rare human genetic developmental disorder, Aicardi-Goutières syndrome (AGS), which mimics viral infection and immune activation (39, 53, 66). A recent study reported that the CD14 + monocytes from AGS patients are highly susceptible to HIV-1 infection, which is consistent with the idea that SAMHD1 restricts HIV replication in myeloid cell types (5).…”
Section: Mechanistic Interactions Between Samhd1 Vpx and Cellular Dmentioning
confidence: 99%
“…Others are advocating the use of chilblain as another diagnostic sign for AGS (38), especially that AGS-associated chilblain lesions has been observed in all five complementation groups. A homozygous large deletion in the SAMHD1 gene was shown to cause multiple mtDNA deletions (43). Compellingly, another de novo dominant negative mutation in TREX1 at the same amino acid residue (D200H) and mutations in SAMHD1 has led to a combination of both AGS and SLE in patients (33,40).…”
Section: Current Genetic Developmentsmentioning
confidence: 99%